The Living Lab on Media Content and Platforms: Results from six months of web browser tracking - Montargil*, Filipe (2021)
The Living Lab on Media Content and Platforms (LLMCP) has developed the LLMCP LisPan project, with the objective of studying the habits and behaviors of Internet users, through an innovative online panel of users using web tracking technology. It was possible to analyze overt online behavior for a sample panel of 70 college students, for six months, and to compare this analysis with their answers to a survey, which additionally was carried out. Results confirm extensive Internet use, but with differences between Friday, Saturday and Sunday, compared to the rest of the week, and the existence of periods of differing intensity, throughout the day. Differences between an “online” dimension of Internet use (search and use of online content) and a “connected” dimension (online interaction with other users) have also been found. It has also been possible to conclude that three-quarters of the participants over-report the frequency of their Internet access.